(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Drinking water, domestic water, commercial water and room illustrate the groundwater crisis. Space is the one concern that is far more critical than the other. The management and space concerns are creating water issues in Delhi. Delhi is the country’s third largest urban area and the third largest populous city. The Yamuna River and groundwater in Delhi are two wells. It is a procedure for groundwater mining and must be told ten days in advance to the district commissioner. There is no authority to reject or screen applications for the District Commissioner. A new tube well is being built every day in Delhi. Under previous regulation, removing groundwater from the areas mentioned was a crime.